A Systematic Review on Anaerobic Textile Industrial Wastewater Treatment: Influence of Processes, Microbial Communities and Bioreactors - Mwizerwa, Innocent Tayari; Wang, Yu; Chen, Xiaoguang (Journal of Environmental Accounting and Management, 2026)
Anaerobic textile wastewater treatment has become popular in industrial textile treatment for decades. Therefore, the influence of processes, microbial community and bioreactor relevance need to be updated. This paper provides reviewed literature of processes, microbial communities and bioreactors used in anaerobic textile wastewater treatment. These include; temperature, organic loading rate (OLR), up flow velocity, sludge retention time (SRT) as well as hydraulic retention time (HRT) and particle size distribution. Archaea and bacteria as the main groups of microbial communities involved in the treatment of textile wastewater compounds have been highlighted. Expanded granular sludge bed reactor, internal circulation reactor (IC), anaerobic baffled reactor (AnBR), membrane coupled high-rate reactors (MCHR), membrane coupled systems, up-flow anaerobic sludge blanket reactor (UASB) and spiral symmetry stream anaerobic reactors (SSSAB) were also reviewed.